2021
DOI: 10.1109/access.2021.3078252
|View full text |Cite
|
Sign up to set email alerts
|

Filtered Multicarrier Waveforms Classification: A Deep Learning-Based Approach

Abstract: Automatic signal recognition (ASR) plays an important role in various applications such as dynamic spectrum access and cognitive radio, hence it will be a key enabler for beyond 5G communications. Recently, many research works have been exploring deep learning (DL) based ASR, where it has been shown that simple convolutional neural networks (CNN) can outperform expert features based techniques. However, such works have been primarily focusing on single-carrier signals. With the advent of spectrally efficient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…It can have significant impact in domains of image classification, image processing and image transmission over networks [41,42]. It will also have cyber-security impact in the domains of health care [43], cloud computing [44,45], image transmission using optical fibre [46][47][48] and deep learning [49].…”
Section: Impact Of Cd-ganmentioning
confidence: 99%
“…It can have significant impact in domains of image classification, image processing and image transmission over networks [41,42]. It will also have cyber-security impact in the domains of health care [43], cloud computing [44,45], image transmission using optical fibre [46][47][48] and deep learning [49].…”
Section: Impact Of Cd-ganmentioning
confidence: 99%
“…A better grasp of how YOLO works is still required. Kang et al [23] suggested a hybrid model using deep features and machine learning classifiers along with the combination of several deep learning approaches with classifiers such as SVM, RBF, KNN, and others [24]. The ensemble feature has aided in the modeling of improved performance.…”
Section: Related Workmentioning
confidence: 99%
“…Deep neural network is one of them and used for predicting the battery life in integration with IoT [44]. Three-step DNA sequence mining is also proposed for optimization of the search results using the machine learning approach [45][46][47][48].…”
Section: Research Goals and Objectivesmentioning
confidence: 99%